Epidemiological analysis of axillary apocrine bromhidrosis in China: a survey from Chinese higher education students - Zhang, Lei; Cheng, Jiaqi; Wang, Cangyu; Zhao, Junhong; Zhang, Cuiping; Li, Haihong (Frontiers in Medicine, 2023)
Background: There are few epidemiological data on axillary apocrine bromhidrosis (AAB) in the Chinese population, making it impossible to accurately estimate its prevalence or impact on individuals. Objective: To estimate the prevalence of AAB in China, and to survey and compare the psychological status of individuals with and without AAB. Methods: Students in several universities in China were surveyed online for AAB, and the prevalence of AAB was calculated. The Symptom Checklist 90 (SCL-90) was used to evaluate the psychological status. Results: The prevalence of AAB in the surveyed students was 7.5% (194/2571). The projected number of Chinese higher education students with AAB was about 3 million. The onset age of AAB was mainly between 11-20 years old (79.90%, 155/194). 68.04% (132/194) of individuals with AAB had a positive family history, and 60.30% (117/194) had wet earwax. Individuals with AAB often felt depression, anxiety, loneliness and social alienation, and scored significantly higher on the nine primary psychological symptom dimensions than individuals without AAB. Conclusions: AAB affects a small proportion but large numbers of Chinese population. China and the West or East-Asia and the West have different perception, recognition and treatment preferences for AAB.